Analisis Rasio Likuiditas dan Rasio Profitabilitas dalam Menilai Kinerja Keuangan pada PT. Bank Pembangunan Daerah Jawa Barat dan Banten Tbk yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2018-2022 - Neng Reni Sulastri; Rola Manjaleni (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
Recent rapid technological developments have influenced the way people use technology to market their products. It also changes the way consumers transact, using payments via transfer or credit card. Banking, as an important part of the economy, also requires standards in financial reporting. Banks, whose wealth consists primarily of financial assets such as stocks and bonds, have goals to achieve. This research aims to evaluate the financial performance of PT. Regional Development Bank of West Java and Banten TBK by analyzing liquidity and profitability ratios. Financial data of PT. West Java and Banten TBK Regional Development Banks from 2018 to 2022 were used in this research. The research method used is a descriptive approach with quantitative analysis, using existing company report data to describe the situation in detail. The liquidity ratios analyzed include the current ratio, quick ratio, cash ratio, cash turnover ratio, and inventory to working capital. The profitability ratios analyzed include GPM, NPM, ROA, ROE and ROI. The research results show that the financial performance of PT. The Regional Development Bank of West Java and Banten TBK during the 2018-2022 period was unsatisfactory because the values of these ratios were still below industry standards. The liquidity ratio shows that the bank is less able to fulfill its short-term obligations, while the profitability ratio shows that the bank is less efficient in generating profits from the assets and capital it owns.